A descriptive study of publicity efforts by non-profit organisations in Singapore, inclusive of a special event for the Singapore film commission. - Choo, Patricia Tse Ning. (2008)
The project studies the use of publicity techniques and specifically the tool of event management in achieving the objectives of non-profit organisations such as the SFC.